Politik Identitas Etnis Toraja sebagai Masalah Teologis: Kasus di Kabupaten Kolaka, Sulawesi Tenggara - Rumbi, Frans Paillin (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2019)
The issue to be examined is identity politics by Torajanese in Kolaka Regency and how to highlight it in terms of Christian political theology. To obtain the data, the writer uses a grounded theory type of qualitative research method. From the results of the research, it appears that identity politics is used to: First, to cultivate compassion or solidarity. Second, realizing the interests of certain elements in the realm of practical politics, especially related to the position in the system of government. Those research show that there is a gap in vision among the community, this situation also triggered internal conflicts between them. The problem needs to be addressed immediately, specifically the author highlights it from the perspective of political theology. Conflict can be overcome if the conflicting parties hold a dialogue to prioritize life values such as love, justice and peace. Abstrak Masalah yang hendak dikaji dalam artikel ini ialah politik identitas orang Toraja di Kabupaten Kolaka dan bagaimana menyorotinya dari segi teologi politik Kristen. Untuk memeroleh data, maka penulis menggunakan metode penelitian kualitatif jenis grounded theory. Dari hasil penelitian, tampak bahwa politik identitas digunakan untuk: Pertama, membudayakan belarasa atau solidaritas. Kedua, mewujudkan kepentingan oknum tertentu pada ranah politik praktis terutama terkait dengan kedudukan dalam sistem pemerintahan. Kedua temuan memperlihatkan adanya kesenjangan visi dalam komunitas, situasi itu turut memicu konflik internal di antara mereka. Masalah tersebut perlu segera diatasi, secara khusus penulis menyorotinya dari perspektif teologi politik. Konflik dapat diatasi jika pihak-pihak yang bertikai mengadakan dialog mengutamakan nilai-nilai kehidupan seperti kasih, keadilan, dan damai sejahtera.